2015
DOI: 10.1161/circep.114.002637
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sinus Rhythm Late Activation Zones and Critical Sites for Scar-Related Ventricular Tachycardia

Abstract: Background It is not known if the most delayed late potentials are functionally most specific for scar-related ventricular tachycardia (VT) circuits. Methods and Results Isochronal late activation maps (ILAM) were constructed to display ventricular activation during sinus rhythm over eight isochrones. Analysis was performed at successful VT termination sites and prospectively tested. 33 patients with 47 scar-related VTs where a critical site was demonstrated by termination of VT during ablation were retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 25 publications
(28 reference statements)
6
115
0
2
Order By: Relevance
“…The median ratio of RMCC ablated per patient was 1 (IQR, 0.6-1). 13 The latest activation ripple is consistent with the latest isochrones of activation in these patients ( Figures 1D-F and 2D). In contrast, Figure 2C shows examples of retrospectively identified RMCC remnants following ablation.…”
Section: Association Of Rmcc Elimination With Outcomesupporting
confidence: 80%
See 1 more Smart Citation
“…The median ratio of RMCC ablated per patient was 1 (IQR, 0.6-1). 13 The latest activation ripple is consistent with the latest isochrones of activation in these patients ( Figures 1D-F and 2D). In contrast, Figure 2C shows examples of retrospectively identified RMCC remnants following ablation.…”
Section: Association Of Rmcc Elimination With Outcomesupporting
confidence: 80%
“…(corresponding to the latest isochrones of RMCC) comprise optimal ablation targets 13,[17][18][19][20]. Current techniques using endocardial and epicardial VT substrate ablation in ARVC provide 71% long-term VT-free survival 21.…”
mentioning
confidence: 99%
“…13,14 Adjustment of the voltage threshold has been used to identify channels of preserved myocardium within scar, but because voltage is annotated to the electrogram peak, these regions are usually formed of far-field signal. 15 Manual tagging of abnormal potentials or manual adjustment of activation time using color-coded isochronal activation maps can highlight local activation through scar, but are challenging with high-density point collection, and annotation as a single activation time is suboptimal at sites with fractionated or multiple late 12 Adjusting the window-of-interest post QRS has been used to highlight sites of late activation but ignores all local signals within the time window spanned by the QRS complex. 16 In this study, we found that RM overcame some of the practical limitations of characterizing the VT substrate using conventional 3-dimensional mapping techniques.…”
Section: Discussionmentioning
confidence: 99%
“…20 In Figure 2B, a multicomponent local electrogram signal is recorded during VT. One component is mid-diastolic and highly fractionated (A), with a lower amplitude than the component activated during the QRS (B). Pacing performed at 10 mA resulted in acceleration of the tachycardia with nearconcealed fusion.…”
Section: Tungmentioning
confidence: 99%